Cool Load Analysis Design Thermoelectric Cooler with Ketapang Leaf Media (Terminalia catappa) - Fachruddin, Faizal; Kamal, Mustopa; Riyadhi, Alwan (Jurnal Teknologi, 2025)
The first thermoelectric effect was discovered in 1821 by T.J. Seebeck. He showed that an electromotive force could be produced by heating a junction between two dissimilar electrical conductors. The Seebeck effect can be demonstrated by making connections between different metal wires (e.g. copper and iron). The thermoelectric module will generate a voltage if the two sides of the surface have different temperatures, namely the hot side and the cold side, otherwise a temperature difference will be generated if the thermoelectric module is voltage supply. Cold load is the amount of heat transferred by the air conditioning system per unit time. The refrigerant load includes the temperature of the incoming and outgoing air, the humidity of the incoming and outgoing air, the mass flow rate of the outgoing air, and the temperature in the cooler. The cold load will directly affect the cooling performance of the machine. A thermoelectric cooler is a cooler that uses the Peltier effect in its system as a heat exchanger. This Peltier element is environmentally friendly because it does not use freon gas for the cooling process, so it is not harmful to the environment. Using a thermoelectric cooler could maintain the product, but in this study ketapang leaf elements were added. This ketapang leaf is an insulator with antibacterial properties. The method used involves collecting temperature and humidity data from the peltier in the cooler. Calculate the mass flow rate of air leaving the peltier and the cooling load on the cooler. Temperature measurements and data collection were carried out over 10 days and divided into three periods, namely morning with an average temperature of 25°C, daytime with an average temperature of 32°C and at night with an average temperature of 25°C. is 28°C. The cooler temperature measurement was performed using the TEC 12706 and TEC 12710 thermoelectric modules. The TEC 12706 type thermoelectric module obtained a final cooler temperature of 22.6°C with test time is 240 minutes. However, the TEC 12710 type thermoelectric module achieved a final cooling temperature of 23.9°C after 240 minutes of testing. These two tests are done at the same time, i.e. at night. The average cooling load on the thermoelectric cooler is 25.16 kJ/s.